Bacterial Pathogens of Silkworm: Impacts and Management Strategies - Qadir, Jasmeena; Bhat, Shabir Ahmad; Rasheed, Showqeena (International Journal of Bio-resource and Stress Management, 2025)
Bacterial diseases affecting silkworms are collectively known as flacherie. It is one of the infectious diseases reported to cause huge crop loss upto tune of 27–35% with significant cocoon yield reduction of 11 to 15 kg 100 dfls-1 annually. It is caused by a wide variety of bacteria belonging to different genera viz. ,Aeromona, Bacillus, Enterobacter, Pseudomonas, Serratia, Streptococcus, and Staphylococcus. The poor quality mulberry leaf with low protein, sucrose or high cellulose makes silkworms comparatively more susceptible to infection by pathogens. Many factors viz., improper rearing house, faulty rearing practises, improper disinfection and hygiene, poor quality of nutrition, host susceptibility, host population density, synergistic association of pathogens and host population density lead to bacterial disease outbreak in the silkworm population. The silkworms appear physiologically weak and flacherie outbreak elicits a heavy toll on sericulture every year. The growth of affected silkworm larvae becomes stunted, flaccid and larvae develop different colours, depending on the species of bacteria involved in causing the infection, become rotten and foul smelling. Microscopic tools help in detection of silkworm pathogens and play a significant role in the management aspects. Many prophylactic measures are adopted to reduce the disease outbreak in silkworms. Antibiotics such as erythromycin, kanamycin, streptomycin, chloramphenicol, Aureomycin, neomycin and tetracycline have been reported to be suppressive against bacterial disease of digestive system. The plant extracts bearing anti-microbial activity can be used to control bacterial diseases in silkworm, B. mori.